Pengaruh Periklanan, Promosi Penjualan, Penjualan Personal, Hubungan Masyarakat dan Pemasaran Langsung Terhadap Keputusan Pembelian di Minimarket: Studi Kasus Konde Mart - Lukia Zuraida; Ardianto Dwi Nugroho (Syntax Idea)
This research aims to determine the influence of Advertising, Sales Promotion, Personal Selling, Public Relations, and Direct Marketing on Purchasing Decisions at the Konde Mart minimarket, sample of 100 respondents. This research uses quantitative with an online questionnaire via Google Form. This research was conducted using multiple linear analysis methods and tested using SPSS Version 25. The test results showed that the advertising variable (X1) had a positive and insignificant effect on purchasing decisions, the Sales Promotion variable (X2) had a positive and significant effect on purchasing decisions, the Personal Sales variable (X3) had a positive and insignificant effect on purchasing decisions, variable Public Relations (X4) has a positive and significant effect on purchasing decisions, the Direct Marketing variable (X5) does not have a positive and significant effect on purchasing decisions.